Evaluation of Waiting Time for Outpatient Prescription Services at the Pharmacy Installation at the Universitas Sumatera Utara Hospital - Muhammad Yunus; Wiryanto; Yuandani (Talenta Publisher, 2020)
The pharmacy installation is one of the units in the hospital that provides. service products and services in the form of prescription services. Prescription service asthe front line of pharmacy services to patients must be managed properly becausethe quality of pharmaceutical prescription service which is generally associated with the speed ingiving service. This research is a descriptive type of research with prospective data collection from March-June 2019 to evaluate the waiting time for outpatient prescription services at the Hospital Pharmacy Installation of the Universitas Sumatera Utara. The data taken were 357 outpatient prescriptions.The results of this study indicate the total average length of time waiting for outpatients for the provision of non-fake drugs at the Pharmacy Installation of Outpatients at the University of Sumatera Utara Hospital at 09.00 - 11.00 is 29.10 minutes, at 11.00 - 13.00 is 34.44. minutes and at 13.00 - finished 42.60 minutes. The average length of waiting time for outpatients for the provision of compound drugs at the Outpatient Pharmacy Installation of the University of Sumatera Utara Hospital at 09.00 - 11.00 is 51.67 minutes, 11.00 - 13.00 hours is 62.27 minutes and at 13.00 - completion was 65.71 minutes. The waiting time for prescription services is ≤ 60 minutes.Based on the results of research conducted at the Outpatient Pharmacy Installation at the University of Sumatera Utara Hospital, non-concocted prescription drugs meet the requirements if the service time speed is ≤ 30 minutes and the concocted drug prescription fulfills the requirements if the service time speed is ≤ 60 minutes.